Development and Social Capital: A Case Study of Selected Malaysian Non-Governmental Organizations (NGOs) - Azeem Fazwan Ahmad Farouk; Azrina Husin (Kajian Malaysia, 2015)
Social scientists continue to grasp for critical factors that foster or impede the development of social capital. This article examines some of these factors based on an investigation of developmental issues in rural Malaysia. Community activists and leaders, NGO staff, and key informants living and working in the designated locality indicated a complex and diverse range of social, cultural, political, and economic issues that have spurred Malaysian NGO involvement in alternative and participatory approaches to development. This situation is partly because the state-led developmental strategy adopted by the Malaysian regime since independence has impeded the development of social capital by curbing civic participation and participatory forms of social organising